Immunostimulatory oncolytic activity of coxsackievirus A11 in human malignant pleural mesothelioma. Issue 3 (22nd November 2022) - Okamura, Koji; Inoue, Hiroyuki; Tanaka, Kentaro; Ikematsu, Yuki; Furukawa, Rie; Ota, Keiichi; Yoneshima, Yasuto; Iwama, Eiji; Okamoto, Isamu
Abstract: Malignant pleural mesothelioma (MPM) is an aggressive solid cancer with a poor prognosis, whereas coxsackievirus A11 (CVA11) is a potential oncolytic virus for cancer treatment. We here investigated the oncolytic activity of CVA11 with human MPM cell lines. CVA11 infection was cytotoxic in all six MPM cell lines examined and showed no or minimal cytotoxicity toward normal human normal cell lines. MPM cells with a higher surface level of intercellular adhesion molecule‐1 (ICAM‐1) expression tended to be more susceptible to CVA11‐induced cytotoxicity, and a neutralizing antibody to ICAM‐1 attenuated such cytotoxicity. CVA11 infection activated signaling by Akt and extracellular signal‐regulated kinase (ERK) pathways, and inhibitors of such signaling also abrogated CVA11‐mediated cytotoxicity. Furthermore, CVA11 infection‐triggered multiple modes of tumor cell death including apoptosis, pyroptosis, and necroptosis, and such death was accompanied by the release or exposure of the proinflammatory cytokine interleukin‐1β and damage‐associated molecular patterns such as calreticulin, high‐mobility group box‐1, annexin A1, and heat shock protein 70, which are hallmarks of immunogenic cell death. Notably, in vivo treatment of human MPM xenografts with intratumoral CVA11 injection resulted in significant suppression of tumor growth in SCID mice, and all mice infected with CVA11 showed no significant change in body weight. Our findings collectively suggest that the oncolytic activity of CVA11 for MPM is dependent on ICAM‐1 as a virus receptor, as well as on Akt and ERK signaling, and that oncolytic virotherapy with CVA11 is a promising treatment modality with immunostimulatory activity for human MPM. Abstract : The authors found that coxsackievirus A11 (CVA11) infection exhibited a marked oncolytic activity in multiple human malignant pleural mesothelioma cell lines in vitro, and that serial intratumoral CVA11 injections into mesothelioma xenografts resulted in significant suppression of tumor growth in SCID mice with tolerability. The authors successfully identified ICAM‐1 as a receptor for CVA11 infection. CVA11 infection‐triggered cytotoxicity was partially dependent on MEK/ERK and PI3K/Akt signaling pathways and manifested multimodal immunogenic cell death with proinflammatory cytokine and DAMPs.